2014
DOI: 10.1016/j.mayocp.2013.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Extracorporeal Shock Wave Myocardial Revascularization Therapy for Refractory Angina Pectoris

Abstract: Objective: To assess the safety and efficacy of extracorporeal shockwave myocardial revascularization (ESMR) therapy in treating patients with refractory angina pectoris. Patients and Methods: A single-arm multicenter prospective trial to assess safety and efficacy of the ESMR therapy in patients with refractory angina (class III/IV angina) was performed. Screening exercise treadmill tests and pharmacological single-photon emission computed tomography (SPECT) were performed for all patients to assess exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 36 publications
(37 reference statements)
1
32
0
Order By: Relevance
“…The current study extends previous smaller clinical trials and showed that ESMR therapy is an effective and safe option for patients with refractory angina pectoris and improves exercise capacity and reduces nitroglycerin use in patients with end-stage ischemic heart disease with no procedural complications or side effects [30,33,34,3739]. The clinical improvement of myocardial ischemia correlates with the SPECT finding that shows a significantly improved myocardial perfusion after the ESMR.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The current study extends previous smaller clinical trials and showed that ESMR therapy is an effective and safe option for patients with refractory angina pectoris and improves exercise capacity and reduces nitroglycerin use in patients with end-stage ischemic heart disease with no procedural complications or side effects [30,33,34,3739]. The clinical improvement of myocardial ischemia correlates with the SPECT finding that shows a significantly improved myocardial perfusion after the ESMR.…”
Section: Discussionsupporting
confidence: 84%
“…However recent randomized study failed to show a beneficial effect of SCS on symptoms as well as functional capacity [30,33]. Moreover SCS is an invasive strategy that can carry some complications such as infections or lead migration or fracture [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other studies, no complications or adverse events were observed [1]. Cassar et al [33] in a multicenter study based in the USA also reported improved symptoms with shockwave therapy, but did not report any change in myocardial perfusion. Most recently, the CELLWAVE trial studied similar patients with ischemic cardiomyopathy who had received bone marrow-derived stem cells and ESMT and found a significant improvement in left ventricular function at 4 months [34].…”
Section: Discussionmentioning
confidence: 52%
“…However a highly skilled professional for targeting the shock waves is needed (hence the technique may not be affordable to all patients) and ESMR's therapeutic impact is somewhat questionable with a noted absence of randomized controlled clinical trials (again placebo effect?) and recent RFA studies showing only borderline to absent improvements of empirically measurable perfusion [36,37].…”
Section: Patient Inclusion Criteriamentioning
confidence: 84%